Implementasi Sistem Informasi Geografis pada Pemetaan Lahan Aset Desa Palembon menggunakan Google Maps API - Aditya Galih Sulaksono (Journal of Information System Research (JOSH), 2023)
Village assets are assets owned by the village. It is necessary to collect, record, and report the data. The village assets consist of several types, one of which is buildings and land. To collect data on building and land assets, a mapping is needed to describe the condition of the distribution area of these assets. Therefore, a web-based Geographic Information System (GIS) design, using the Laravel Framework utilizing the Google Maps Javascript API as a digital map provider and MySQL as a database. This system is used to fix the problems with data collection, recording, and reporting the asset data.